Rethinking ICT Integration in Indonesian Schools: The Role of Digital Self-Learning Beyond Institutional Support - Henry Pandia; Sintaria Sembiring (CV Media Inti Teknologi, 2026)
Purpose of the Study: This study examines the relationships among Digital Self-Learning (DSL), Institutional Support (IS), Professional Development (PD), and Technology Integration (TI) among Indonesian teachers. Specifically, the study investigates how teachers' autonomous digital learning behavior contributes to classroom-level ICT integration beyond formal institutional and training mechanisms.Methodology: A quantitative cross-sectional survey was conducted involving 221 Indonesian in-service teachers. The study applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data, examine relations among the proposed constructs, and explore the mechanisms underlying technology integration.Main Findings: Digital Self-Learning is the strongest predictor of both Professional Development and Technology Integration. Institutional Support significantly influences Digital Self-Learning but does not directly affect Technology Integration, suggesting that institutional conditions primarily contribute through enabling teachers' self-directed learning behavior. Professional Development further strengthens Technology Integration, whereas demographic variables such as age, gender, and educational level exert little influence. Although the proposed model confirmed substantial explanatory power, its out-of-sample projecting performance was limited. Therefore, the findings should be interpreted primarily from an explanatory rather than a predictive perspective.Novelty/Originality of this Study: The novelty of this study lies in its reconceptualization of ICT integration as a behaviorally driven process in which Digital Self-Learning functions as the central mechanism linking institutional conditions, professional growth, and classroom technology integration. The findings contribute to the growing discourse on teacher digital capability and offer practical insights for developing more adaptive and sustainable ICT integration strategies in educational settings.